Other Oxides Pre-removed from Bangka Tin Slag to Produce a High Grade Tantalum and Niobium Oxides Concentrate. Issue 1 (May 2016) - Permana, S; Soedarsono, J W; Rustandi, A; Maksum, A
Abstract: Indonesia, as the second largest tin producer in the world, has a byproduct from the production of tin. This byproduct is in the forms of tin slag containing tantalum pentoxide (Ta2 O5 ) and niobium pentoxide (Nb2 O5 ). This study focuses on the recovery of tantalum pentoxide and niobium pentoxide from the tin slag. In the process, one part of the tin slag sample was sieved only (BTS), and the other was roasted at 900°C, water quenched and then sieved (BTS-RQS). Samples BTS and BTS-RQS were characterized by thermo gravimetric analysis (TGA) and X-ray flourence (XRF). One part of BTS-RQS sample was dissolved in hydrofluoric acid (HF) and the other was dissolved in hydrochloric acid (HCl), washed with distilled water, then dissolved into sodium hydroxide (NaOH). Each sample was characterized by using XRF. The BTS sample produced the highest recovery of 0.3807 and 0.6978% for Ta2 O5 and Nb2 O5, respectively, from the particle size of -1.00+0.71 and a fraction of 47.29%, while BTS-RQS produced the highest recovery of 0.3931 and 0.8994% for Ta2 O5 and Nb2 O5, respectively, on the particle size of -0.71+0350 and a fraction of 21%. BTS-RQS, dissolved with 8% hydro fluoride acid, yields tantalum pentoxide and niobium pentoxide with a ratio of 2.01 and 2.09, respectively. For the sample BTS-RQS dissolve first with 6M hydrochloric acid, washed with distilled water, then dissolved with sodium hydroxide 10M, the yield ratios are 1.60 and 1.84 for tantalum pentoxide and niobium pentoxide, respectively. In this study, it is found that the dissolution by using hydrofluoric acid 8% yields the best ratio.